Changes in lake-sediment stratigraphy associated with late glacial climate change: examples from western Nova Scotia - Spooner, Ian (Atlantic Geology, 1998)
An investigation of lake-sediment stratigraphy in western Nova Scotia has focused on determining the environmental response to late-glacial climate change. Sediment records from Ave headwater lakes were recovered and sediment stratigraphy from four of the lakes was used to reconstruct late-glacial environments for this region. Results from Sand Lake and Canoran Lake (South Mountain) indicate that the South Mountain was deglaciated by about 11,500 B.P. The North Mountain was deglaciated slightly earlier. All cores contained till (unit 1) which was overlain by a fine-grained diamicton (unit 2) that was deposited after ice had receded. A gyttja with varying mineral sediment concentrations (unit 3) overlies unit 2. Unit 2 is interpreted as sediment that was transferred to the basin as the basin and catchment stabilized. The North Mountain sites are characterized by lack of a Younger Dryas-equiva-lent loss-on-ignition or mineral oscillation. The South Mountain sites both contain a thin (2 cm) Younger Dryas-equivalent mineral horizon (unit 4) bounded above and below by sandy gyttja (units 3 and 5). Image and grain size analysis of units 3,4 and 5 indicate that these units differ primarily in their amounts of fine silt and clay, as mavimiim grain size is similar in each unit. This result indicates that changes in sediment transfer mechanisms in response to climate change were subtle. The formation of unit 4 (YDimh) was primarily a consequence of intrabasin sediment transfer and reduced productivity; an increase in the extent and/or duration of lake ice cover may have been an important factor. The catchment response to Younger Dryas climate change in western Nova Scotia was probably subdued. Though aufeis and perennial snow cover may have existed at some sites, the presence of Younger Dryas-equivalent glacial ice in western Nova Scotia is unlikely.